Pemanfaatan Media Sosial dalam Meningkatkan Usaha Ritel Sekolah - Rahmawati Alwi; Muhammad Faiqh Akbar; Amirah Azmi; Delia Rasdiane; Siti Dalillah; Macih Macih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research is motivated by the increasing use of social media as a digital marketing tool, which is considered potential to support the development of school retail businesses, especially in Vocational High Schools. The purpose of this study is to analyze the use of social media in improving the performance of school retail businesses at SMK Bumi Sejahtera Cibungbulang, reviewed from the aspects of marketing reach, interaction with consumers, and its impact on sales. This study uses a qualitative method with a case study approach, through data collection techniques in the form of observation, interviews, and documentation of managers and related parties in the school retail business. The results and discussion indicate that the use of social media, especially through visual content and two-way communication, can increase the visibility of retail businesses, expand market reach, and encourage increased purchasing interest and consumer loyalty, despite still facing limitations in digital literacy and consistent content management. The conclusion of this study confirms that social media has a strategic role in the development of school retail businesses and has the potential to be an effective means of learning entrepreneurship if supported by increased human resource capacity and sustainable digital strategy management.